MCNP model of the EEAE ACCUSCAN Whole Body Counter - Sarlikiotis, N.; Potiriadis, C.; Nikolaki, M.; Stamatelatos, I. E. (HNPS Advances in Nuclear Physics, 2019)
Monte Carlo simulations and verification measurements for the efficiency calibration of the ACCUSCAN shadow-shield type Whole Body Counter (WBC) of the Greek Atomic Energy Commission (EEAE) are presented. A model of the counter and RMC-II anthropomorphic phantom was developed using the MCNP code. Full energy peak efficiencies for different phantom positions were calculated for 60Co and 137Cs sources. The deviations between computational and experimental efficiencies were found to be less than 12 % for 60Co and 4 % for 137Cs for the Ge detector and less than 25 % for 60Co and 4 % for 137Cs for the NaI detector. This work contributes to the accurate quantification of internal contamination in individuals accidentally exposed in Greece by the Greek Atomic Energy Commission Laboratories and moreover demonstrates the effectiveness of using computational tools for understanding the calibration of radiation detection systems used for in vivo monitoring.